P83 Combined liver and kidney transplantation: a single centre experience. (6th September 2011) - Smith, M; Rye, K; Haldane, T; Gunson, B; Bramhall, S; Mutimer, D
Abstract : Introduction: Combined liver kidney transplantation (CLKT) is an accepted approach to management of patients with dual organ pathology, but may be associated with significant additional post-operative morbidity and mortality in comparison with transplantation of either organ alone. Aim: To analyse the experience of CLKT at a single centre. Method: Retrospective analysis of all CLKTs performed at our centre between May 1994 and August 2010. Data collected included demographics, indications for CLKT, surgical techniques, post-transplant complications and patient/graft survival. Results: Of 2130 liver transplants (LT) performed there were 24 CLKTs—12 male with median age 52 years, Child-Pugh score 7 and MELD 19. Indications for LT were polycystic liver disease 11 (46%), cirrhosis 7 (29%), hepatocellular carcinoma 2 (8%), recurrent PSC/PBC 3 (12%), oxalosis 1 (4%). The indications for kidney transplantation (KT) were polycystic kidney disease 10 (42%), calcineurin-inhibitor toxicity 4 (17%), chronic kidney graft failure 4 (17%), IgA nephropathy 3 (13%), diabetes 1 (4%), Type II hyperoxaluria 1 (4%), glomerulonephritis 1 (4%). Five patients had prior KT; four chronic graft failure, 1 calcineurin-inhibitor toxicity. 12 patients (50%) were dialysis-dependent pre-transplantation. During a median follow-up of 1223 days (IQR 550–2264 days) 5 patients died (overall survival 79.2%) with a median time from CLKT to death 947 days (range 4–2373 days). Causes of death: primary non-function of the liver (1), cardiac complications (2) and de novo cancer (2). Seven patients (29%) had at least one episode of histologically proven acute cellular rejection of the liver and 1 (4%) acute renal rejection. Cumulative 1, 3 and 5-year patient, liver graft and kidney graft survival were 96%, 85%, 75%; 86%, 79%, 62% and 91%, 85%, 75% respectively. 3 patients required further liver transplantation (2 hepatic artery thrombosis, 1 primary non-function). 13 patients required haemodialysis post-operatively. At 3-month follow-up, survivors had median creatinine and eGFR of 129 μmol/l and 48 ml/min respectively; 1 patient still required dialysis. At 1 year and 5 years median creatinine and eGFR were 134 μmol/l and 43 ml/min, 155 μmol/l and 38 ml/min respectively. 1 patient resumed haemodialysis 4640 days after CLKT and is on the waiting list for renal re-transplantation. Conclusion: CLKT in this cohort had favourable outcomes with excellent patient and graft survival (both organs). Although the number of patients in our study is relatively few, 5-year kidney graft survival rates do not appear inferior to published data for patients undergoing renal transplantation alone.